In vitro antibacterial efficacy of some important traditional medicinal plants in India against Escherichia coli and Staphylococcus aureus strains - Khan, Abdul Viqar; Ahmed, Qamar Uddin (Academic Journals, 2013)
Historically, bacteria have been the cause of some of the most deadly diseases and widespread epidemics of human civilization. Many plants are known for their ethno- medicinally importance in the region of western Uttar Pradesh, India but their sensitivity against hospital isolated Escherichia coli(E.coli) and Staphylococcus aureus (S. aureus) human pathogenic bacterial strains has not been examined properly.E. coli and S. aureus are the two most common bacteria responsible for chronic infections among patients across the world. Hence, this communication emphasized upon the sensitivity of methanol (MeOH) and aqueous (AQ) extracts of 24 plant species against S. aureus ATCC 25953, E. coli MTCC 739 and four clinical isolates including S. aureus (Sa1),S. aureus (Sa2),E. coli(Ec1) and E. coli (Ec2)using disc diffusion and agar dilution method. Methanol extracts of the plants exhibited potent antibacterial activity against organisms taken into consideration. The results also support ethno-medicinal use of plants reported earlier. Present study revealed that studied plant extracts could be efficacious remedial herbal antibiotics, particularly both in controlling Gram-positive and Gram-negative human pathogens.